Reconfigurable Antennae: VO2‐Based Reconfigurable Antenna Platform with Addressable Microheater Matrix (Adv. Electron. Mater. 9/2017). (11th September 2017) - Gerislioglu, Burak; Ahmadivand, Arash; Karabiyik, Mustafa; Sinha, Raju; Pala, Nezih
Abstract : In article number1700170, Burak Gerislioglu and co‐workers successfully introduce a novel, smart, and reconfigurable antenna platform that can control virtually the entire planar antenna pattern through a phase transition process with an integrated individually addressable microheater matrix. Combined with the low‐temperature and fast phase‐transition process of vanadium dioxide (VO2 ), this technique opens new doors to the possibility of creating novel reconfigurable antenna structures with reduced phase‐change temperature increment and time.